Use what you've got : and other business lessons I learned from my mom - Corcoran, Barbara (Barbara Ann); Littlefield, Bruce (Bruce Duanne) (New York : Portfolio, 2003)
A founder of the Corcoran Group real estate company describes her hard-working childhood and the lessons she learned from her mother and through her business experiences that enabled her to become successful
10 kids, 1 bath -- If you don't have big breasts, put ribbons on your pigtails -- Paint the rocks white and the whole yard will look lovely -- If the sofa is ripped, cover it with laughter -- Use your imagination to fill in the blanks -- Offer the bigger piece, and yours will tasteeven better -- Put the socks in the sock drawer -- If there's more than one kid to wash, set up a bathtime routine -- If you want to be in two places at once, borrowa reel-to-reel -- It's your game, make your own rules -- There's always room for one more -- Go play outside -- When the clubhouse is quiet, they're probably not making spaghetti -- If you want to be a cheerleader, you better know the cheers -- Go stand next to Nana and see how big you are! -- If you want to get noticed, write your name onthe wall -- Sweep the corners and the whole house stays clean -- In a family, everyone helps mash the potatoes -- Moms can't quit -- Where there are ten buyers and three puppies, every dog is the pick of the litter -- Jumping out the window will make you either an ass or a hero -- You have the right to be there -- You've got to bully a bully -- Never be ashamed of who you are -- The joy is in the getting there -- What I wish every salesperson knew
Includes index.
Keywords: Corcoran, Barbara; Women real estate agents -- United States -- Biography; Real estate business -- United States